Soft Tissue Sarcomas of the Arm – Oncosurgical and Reconstructive Principles within a Multimodal, Interdisciplinary Setting - Koulaxouzidis, Georgios; Simunovic, Filip; Bannasch, Holger (Frontiers in Surgery, 2016)
Soft tissue sarcomas (STS) s of the upper extremity represent a severe threat for the patient and a difficult task for the treatment team. Due to the complex anatomy of the arm, most sarcomas involve valuable functional structures. Nonetheless, a large portion of the patients can be treated in a limb-sparing manner, and surgery is the mainstay of local tumor control. This review gives an overview of the disease entities and their epidemiology, on necessary patient work-up, staging and imaging modalities, as well as the importance of interdisciplinary decision-making. The surgical therapy and principles of tumor excision are outlined, as well as reconstructive options. Furthermore, adjuvant treatments are discussed with a special focus on the various application techniques for radiation therapy. In spite of established treatment algorithms, each case is an individual challenge and individually tailored therapy is required. This aspect is illustrated by presenting three comprehensive cases demonstrating useful strategies. A summary of the relevant literature is given.